The Influence of DMPA on the Instability of the Menstrual Cycle of KB Acceptors by Injection in Cikulur Public Health Centre Workspace in 2022 - Iin Rosita; Nur Anita (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Depo-Medroxyprogesterone Acetate (DMPA) is a contraceptive with a 150mg dose administered every three months by injection via intramuscular. The mechanism is to prevent ovulation by thickening the cervical mucus resulting in the endometrium being non-optimal for implantation and accelerating ovum transport inside the fallopian tube. One of The side effects of contraception using DMPA is the disruption of the menstrual cycle. Primary health data in 2018 shows that quarterly injected contraceptives as the most used contraception (42,2%). The research goal is to analyze the effects of DMPA on the instability of the menstrual cycle of KB acceptors by injection in the Cikulur public health center workspace year 2022. Methods: The research is a form of analytical approach using the cross-sectional research method done in November 2022. The population of this research consists of quarterly KB acceptors in the Cikulur public health center consisting of 1.646 people. The sampling method used is an accidental sampling technique of 94 people. The instrument of this research is a questionnaire. The data analytic used is chi-square. Result: This research shows there is a relationship between age and the instability of the menstrual cycle with a p-value of 0,000; occupation with the instability of the menstrual cycle with a p-value of 0,006; the duration of use with the instability of the menstrual cycle with a p-value 0,000; medical history with the instability of menstrual cycle with a p-value 0,000; and lastly re-injection compliance with the instability of menstrual cycle with a p-value 0,000. Conclusion: There is a relationship between age, occupation, duration of use, and re-injection compliance with the instability of the menstrual cycle. A piece of advice for acceptors, the result of this research could be regarded as informational material on the side effects that might occur under the usage of KB injection by DMPA.